Complex formation in binary propionic acid-triethylamine mixtures: A dielectric relaxation and titration study - Orzechowski, K.; Pajdowska, M.; Fuchs, K.; Kaatze, U. (The Journal of chemical physics, 2003)
Complex (dielectric) permittivity spectra of propionic acid-triethylamine mixtures have been measured using four different frequency domain methods to cover the frequency range from 1 MHz to 40 GHz. At 20 °C spectra have been determined at eight mole fractions xb of base between 0.11 and 0.8. For one mixture (xb=0.3) measurements have been performed at ten temperatures between −20 °C and 25 °C. Additionally, the extrapolated low frequency (static) permittivity of the propionic acid triethylamine system has been obtained at 0⩽xb⩽1 from titration measurements in the frequency range between 1 MHz and 1 GHz. The spectra exhibit a dielectric relaxation in the microwave region, subject to a small unsymmetric relaxation time distribution, and an extrapolated high frequency permittivity ε(∞) which noticeably exceeds the squared optical refractive index nD2. The microwave relaxation is discussed in terms of acid–base complexes in the liquid, including proton transfer complexes. The dielectric spectra do not evidence a clear stoichiometric composition of the complex structures. The gap between ε(∞) and nD2 is assigned to significant contributions from atomic polarization and the dielectric dispersion due to the reorientational motions of dipolar acid and base molecules.